2019
DOI: 10.1136/bmjopen-2018-025135
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of clinical outcome reporting in randomised controlled trials of burn care

Abstract: IntroductionSystematic reviews collate trial data to provide evidence to support clinical decision-making. For effective synthesis, there must be consistency in outcome reporting. There is no agreed set of outcomes for reporting the effect of burn care interventions. Issues with outcome reporting have been identified, although not systematically investigated. This study gathers empirical evidence on any variation in outcome reporting and assesses the need for a core outcome set for burn care research.MethodsEl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 197 publications
1
32
0
Order By: Relevance
“…Therefore, the quality of each study will not add any additional value to this review. This is consistent with other systematic review of outcomes reported in different medical and surgical conditions 28–30…”
Section: Methods and Designsupporting
confidence: 93%
“…Therefore, the quality of each study will not add any additional value to this review. This is consistent with other systematic review of outcomes reported in different medical and surgical conditions 28–30…”
Section: Methods and Designsupporting
confidence: 93%
“…What is more, both experimental and especially clinical studies on burn treatment used different outcome issues or different definitions, respectively, to assess the same outcome issues, while results were evaluated at different time points after the injury [ 71 , 73 ]. In addition, like all reviews of clinical studies in burns, we had to face the heterogeneity of basic parameters including epidemiology, comorbidity, as well as type, degree, TBSA and localization of the burn.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, like all reviews of clinical studies in burns, we had to face the heterogeneity of basic parameters including epidemiology, comorbidity, as well as type, degree, TBSA and localization of the burn. Young and colleagues, in a recent systematic review of burn treatment, suggested the development of a core outcome set (COS) enabling the comparison of results of studies on burn treatment [ 73 ]. This basic problem when designing trials in burn patients applies also for HBO: Only two clinical studies were randomized including a total of 16 [ 24 ] and 15 patients [ 25 ], respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In burns, the potential of exercise to induce positive effects on energy expenditure, muscle mass and insulin sensitivity has also been investigated, albeit largely in the post-discharge phase and predominantly in paediatric patients [ 16 , 18 , 20 , 23 , 24 , 61 ]. However, the use of exercise for these purposes in adults as part of inpatient care continues to be a largely unexplored, yet promising, area of future research [ 62 ]. Our data shows that metabolic outcomes are not consistently used as therapeutic exercise targets and that more guidance is needed to reach consensus about the role exercise can play in the metabolic management of burn patients.…”
Section: Discussionmentioning
confidence: 99%